Constructing the hierarchical TiN@ZIF-8 hybrid for improving the mechanical and tribological performance of fabric composites. (April 2022) - Liu, Meng; Zhang, Zhaozhu; Wang, Yanling; Li, Peilong; Yang, Mingming; Yuan, Junya
Abstract: Herein, TiN@ZIF-8 hybrid with hierarchical structure was constructed by in situ growth of Zeolitic Imidazolate Frameworks-8 (ZIF-8) onto the TiN surface via a PDA/PEI (polydopamine/polyethyleneimine) intermediate layer. The characterization of structure and chemical composition affirmed the successful assembly of TiN@ZIF-8 hybrid and the specific surface area of TiN@ZIF-8 hybrid showed a sharp increase from 3.5 m 2 /g for pristine TiN to 183.4 m 2 /g. The resulted TiN@ZIF-8 hybrid was aimed at strengthening the mechanical and tribological properties of fabric composites. The results demonstrated that the tensile strength of TiN@ZIF-8/fabric composites presented an increase by 48% due to the stress transfer and reinforcement of TiN@ZIF-8. Additionally, the incorporation of TiN@ZIF-8 restricted the moving of resin molecular chain and escape of decomposition products, contributing to the improvement in heat resistance of fabric composites. Friction and wear tests indicated that the abrasion resistance of TiN@ZIF-8/fabric composites was significantly improved in comparison with pristine composites because the ZIF-8 loaded on the surface of TiN made for a more even dispersion of TiN, and the introduction of TiN@ZIF-8 contributed to forming a uniform, dense transfer film due to the synergistic enhancement between TiN and ZIF-8. Graphical abstract: Image 1 Highlights: The hierarchical TiN@ZIF-8 hybrids were constructed via an in-situ growth. The thermal and mechanical properties of TiN@ZIF-8/phenolic composites were enhanced signally. Excellent tribological properties of TiN@ZIF-8/phenolic composites were obtained. The synergistic reinforcing effect of TiN and ZIF-8 for phenolic matrix was prominent.